Modified filler for asphalt mixture and preparation method thereof

By using modified fillers in asphalt mixture and combining mechanical force chemical dispersion technology, the problem of poor adhesion between aggregate and asphalt is solved, and the performance of asphalt mixture is significantly improved, including denseness, water stability and high temperature stability.

CN119899017AActive Publication Date: 2025-04-29ZHEJIANG EXPRESSWAY MAINTENANCE CO LTD

Patent Information

Application Number
CN202510115802.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-24
Publication Date
2025-04-29
Estimated Expiration
2045-01-24

AI Technical Summary

Technical Problem

The adhesion between aggregate and asphalt in existing asphalt mixtures is poor, resulting in poor pavement performance, difficulty in controlling porosity and compaction, and affecting the pavement seepage coefficient and durability.

Method used

A modified filler is used to combine limestone ore powder, sludge powder, steel slag powder, phosphogypsum, bauxite and other materials, and to combine composite interface modifiers and dispersants to perform dispersion modification under mechanical chemical effects, improve the dispersion and interface performance of the filler and enhance the adhesion between aggregate and asphalt.

Benefits of technology

It significantly improves the adhesion performance between aggregate and asphalt, improves the density, water stability, peel resistance and high temperature stability of the asphalt mixture, and extends the service life of the road surface.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005257793280000091
    Figure BDA0005257793280000091
  • Figure BDA0005257793280000101
    Figure BDA0005257793280000101
  • Figure BDA0005257793280000102
    Figure BDA0005257793280000102
Patent Text Reader

Abstract

The invention belongs to the technical field of road asphalt, and discloses a modified filler for an asphalt mixture and a preparation method of the modified filler. The brick is characterized by being prepared from the following raw materials in parts by weight: 30-40 parts of limestone mineral powder, 25-35 parts of slaked lime, 15-20 parts of steel slag powder, 10-15 parts of phosphogypsum, 5-8 parts of bauxite, 0.5-0.8 part of a compound interface modifier and 0.3-0.5 part of a dispersing agent, the filler is uniformly coated with the composite interface modifier and the dispersing agent under the action of a mechanical force chemical effect, the interface performance is constructed in a micronized modified filler interface, the compatibility of the modified filler and asphalt is good, the surface potential of the aggregate is greatly reduced, the aggregate is easily and uniformly adhered, and the separation of the filler and the aggregate is avoided. The water stability of the asphalt mixture is obviously improved. And due to the application of the modified filler, the range of aggregate selection of the asphalt mixture is wider, local materials can be used, and more types of aggregates are promoted to be applied to the asphalt mixture.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of road asphalt, in particular to asphalt mixture, and in particular to a modified filler for asphalt mixture and a preparation method thereof. Background Art

[0002] Asphalt mixture is a road material made of aggregate, asphalt, mineral powder and other materials mixed in a certain proportion. As asphalt mixture has good elasticity, wear resistance and anti-skid properties, it is effective in reducing driving noise and improving driving comfort and safety. At present, asphalt mixture has been widely used in highways, urban roads, bridges, tunnels, etc.

[0003] According to existing engineering use, a large number of various aggregates are used in asphalt mixtures. For example, high-quality basalt and diabase aggregates are alkaline and have good adhesion to asphalt, but this type of aggregate is rare. When used in actual projects, the aggregates used in large quantities are all locally sourced. Aggregates with large reserves and wide distribution are mainly acidic or neutral aggregates such as granite, slate, andesite, and quartzite. These aggregates have poor adhesion to asphalt, which can easily lead to poor performance of asphalt pavement after paving, thereby limiting the use of aggregates. In addition, the gradation of aggregates used in asphalt mixtures used in actual projects fluctuates greatly. Even within the gradation range specified in the specification, it is difficult to construct the optimal gradation due to the complexity of the aggregates themselves. Ultimately, the porosity of the asphalt pavement is difficult to control, and the pavement is not easy to compact, which ultimately affects the water permeability coefficient and durability of the asphalt pavement. At present, water damage to asphalt pavement layers is the main factor affecting the life of the pavement. Due to the insufficient adhesion between asphalt and aggregate, the aggregate surface separates from the asphalt under the penetration of external rainwater, thereby reducing the mechanical strength of the pavement and causing loose sand and gravel, rutting, potholes and other defects.

[0004] Aggregate is the most used material in asphalt mixture, accounting for about 90% in general, so it is usually obtained from nearby materials for construction. The mineral composition, morphology, specific surface area, etc. of aggregates will seriously affect the performance of asphalt mixtures. For example, andesite is a neutral aggregate with a low content of high-valent cations, and its chemical adsorption with asphalt is unstable, resulting in poor adhesion, which affects the water stability and durability of asphalt mixtures. In particular, aggregates with a high silica content are obviously hydrophilic and oleophobic, have poor adhesion to asphalt, and are easy to absorb water, causing water on asphalt pavement to easily penetrate the asphalt film and be adsorbed by the aggregate, resulting in the separation of aggregates and matrix asphalt, causing cracking of the pavement and reducing the service life of the pavement. For example, granite, which is abundant in various places, is the main aggregate for paving asphalt pavements because of its hard texture, wear resistance and anti-skid. However, since granite is an acidic rock with a high surface negative charge potential, its adhesion to asphalt is limited. When it is used for road paving and is subjected to water erosion, the asphalt and aggregate are easily separated, resulting in a significant reduction in stability when exposed to water, cracking, roughness, and unevenness on the road surface, and even the falling of stones.

[0005] Prior art has disclosed that limestone powder can be used as a filler in asphalt mixture to improve the stability of asphalt mixture. Limestone powder is an alkaline mineral that can achieve a good thickening effect on asphalt mixture, increase the cohesiveness of the mixture, and improve the stability of asphalt mixture. It can greatly enhance the bearing capacity and durability of the road surface by filling voids and microcracks. However, for aggregates with poor adhesion, complex varieties, and unstable grading, single limestone powder or slaked lime has limited effect on improving the cohesiveness between asphalt and aggregate.

[0006] The root cause of water damage to asphalt pavement is the poor adhesion between asphalt and aggregate. In order to promote the use of local aggregates and expand the adaptability of aggregates, it is necessary to further enhance the adhesion between asphalt and aggregates, so as to ensure the density, water stability, anti-stripping and high temperature stability of asphalt mixtures. In view of this, the present invention proposes a modified filler for asphalt mixtures. Summary of the invention

[0007] In order to use aggregates in a wider range of asphalt mixtures, enhance the adhesion between aggregates and asphalt, and improve the compactness, water stability, anti-stripping and high temperature stability of asphalt mixtures, the present invention proposes a modified filler for asphalt mixtures, the modified filler has excellent dispersibility and interface properties, good compatibility with asphalt, can evenly adhere to aggregates, reduce the surface potential of aggregates, so that aggregates with poor adhesion can be well bonded with asphalt; in particular, by mechanically chemically dispersing the modified filler, the dispersibility and interface properties of the filler can be enhanced, and the aggregate can be evenly dispersed and wrapped to avoid segregation, improve the adhesion between asphalt and aggregates, and promote the self-compactness and strength of asphalt mixtures, thereby improving the water stability of asphalt mixtures. Further, a preparation method for the modified filler for asphalt mixtures is proposed.

[0008] In order to achieve the above object, the present invention adopts the following technical solution:

[0009] The first purpose of the present invention is to provide a modified filler for asphalt mixture, characterized in that it is composed of the following raw materials in parts by weight: 30-40 parts of limestone powder, 25-35 parts of slaked lime, 15-20 parts of steel slag powder, 10-15 parts of phosphogypsum, 5-8 parts of bauxite, 0.5-0.8 parts of composite interface modifier, and 0.3-0.5 parts of dispersant; wherein:

[0010] The composite interface modifier is a composite of a titanate coupling agent and / or an aluminate coupling agent and sodium oleate in a mass ratio of 1-3:1;

[0011] The dispersant is at least one of sodium tripolyphosphate and sodium hexametaphosphate;

[0012] The modified filler for asphalt mixture is prepared by the following method:

[0013] (1) adding limestone powder, slaked lime, steel slag powder, phosphogypsum and bauxite into a 1# high-speed mixer and mixing them uniformly; conveying them to a microwave drying tunnel box through a fully enclosed pipeline system, and drying them at a controlled temperature of 120-130° C. to obtain a premix;

[0014] (2) The premix, composite interface modifier and dispersant are added to the No. 2 high-speed mixer and mixed evenly. The mixture is then transported to the continuous airflow fine machine through a fully enclosed pipeline system. The classification speed of the continuous airflow fine machine is controlled to generate a high-speed airflow through high-speed rotation, forming a vortex in the pulverizing chamber. The premix enters the pulverizing chamber quantitatively from the feed port. Under the action of the vortex, collision, friction and shearing occur between the premix particles. At the same time, the mechanical and chemical effects of the composite interface modifier and dispersant modify the fine powder during pulverization, thereby achieving continuous dispersion modification. The mixture is collected in a bag and connected to the finished product bin to obtain a modified filler for asphalt mixture with a D80 particle size of less than 10 μm.

[0015] Preferably, the D50 particle size of the limestone powder is less than 50 μm.

[0016] Preferably, the slaked lime D50 particle size is less than 50 μm; slaked lime has extremely high activity. After being refined and interfacially modified, the modified slaked lime is added to asphalt, and the calcium ions therein promote the deposition of asphalt on the aggregate surface to form a film. The calcium ions accumulate on the aggregate surface and combine with the acid in the asphalt to form a water-insoluble salt, which promotes the anti-stripping ability of asphalt and aggregate. It not only improves the bonding strength of the asphalt mixture, but also fills the micro-voids of the asphalt mixture in the form of powder, improves the compactness of the aggregate, thereby improving the bonding force between the aggregate and the asphalt, and further enhancing the self-compacting property of the asphalt pavement.

[0017] Preferably, the steel slag powder has a particle size D50 of <50 μm, a basicity of greater than 2.0, and an apparent density of 2.56-2.75 g / cm 3 ; Steel slag powder has a higher specific surface area and alkalinity, which makes it easier for asphalt to gather on the steel slag powder and enhances the adhesion performance of asphalt; at the same time, steel slag powder can promote the density and wear resistance of asphalt pavement.

[0018] Preferably, the D50 particle size of the phosphogypsum is less than 50 μm. Phosphogypsum is a by-product of phosphate fertilizer production, and its main component is calcium sulfate dihydrate (CaSO4·2H2O). Phosphogypsum can help increase the melting point and viscosity of asphalt, thereby improving the high-temperature stability of asphalt mixture.

[0019] Preferably, the bauxite D50 particle size is less than 50 μm; bauxite is composed of aluminum hydroxide, which exhibits positive charge under alkaline conditions, and can be used in aggregates to significantly reduce the surface potential of negatively charged aggregates, and has good adhesion to aggregates. Aggregates adhered with ultrafine bauxite come into contact with carboxylic acid anions in asphalt, thereby firmly bonding the asphalt to the aggregate surface.

[0020] Preferably, the composite interface modifier is a composite of a titanate coupling agent and sodium oleate in a mass ratio of 2:1.

[0021] Preferably, the composite interface modifier is a composite of an aluminate coupling agent and sodium oleate in a mass ratio of 3:1.

[0022] Preferably, the composite interface modifier is a composite of a titanate coupling agent, an aluminate coupling agent, and sodium oleate in a mass ratio of 2:1:1.

[0023] Further preferably, the titanate coupling agent is a chelated titanate coupling agent, which is easy to combine with the hydroxyl group on the surface of the filler to make the filler hydrophobic; the other end can be entangled with asphalt, thereby improving the interfacial solubility with asphalt, and is used to modify the filler to ensure stability in a wet environment; such as at least one of the grades YB-301, JN-201, and T3-1.

[0024] More preferably, the titanate coupling agent is a monooxyalkyl titanate coupling agent, such as at least one of YB-203, YB-201, NDZ-101, HY-102, and JTW-101.

[0025] More preferably, the aluminate coupling agent is selected from the F series, such as at least one of F-1, F-2, F-3, and F-4.

[0026] Titanate coupling agents and aluminate coupling agents have good chemical adsorption with alkaline minerals, which can give fillers good interfacial compatibility. Fillers modified with sodium oleate have good hydrophobic properties, which help promote the uniform dispersion of fillers in the asphalt matrix and improve the adhesion with asphalt. Through the composite interfacial modifier, under the action of mechanical force and chemistry, the coating composite modification can be efficiently achieved.

[0027] The modified filler obtained by interface modification and ultra-dispersion treatment has an ultra-fine interface effect. The modified filler not only has good compatibility with asphalt, but also gives the aggregate surface activity, prompting the asphalt to react with the active components on the aggregate surface, effectively enhancing the adhesion between the asphalt and the aggregate.

[0028] Another object of the present invention is to provide a method for preparing the above-mentioned modified filler for asphalt mixture, characterized in that the specific preparation method is as follows:

[0029] (1) adding limestone powder, slaked lime, steel slag powder, phosphogypsum and bauxite into a 1# high-speed mixer and mixing them uniformly; conveying them to a microwave drying tunnel box through a fully enclosed pipeline system, and drying them at a controlled temperature of 120-130° C. to obtain a premix;

[0030] (2) The premix, composite interface modifier and dispersant are added to the No. 2 high-speed mixer and mixed evenly. The mixture is then transported to the continuous airflow fine machine through a fully enclosed pipeline system. The classification speed of the continuous airflow fine machine is controlled to generate a high-speed airflow through high-speed rotation, forming a vortex in the pulverizing chamber. The premix enters the pulverizing chamber quantitatively from the feed port. Under the action of the vortex, collision, friction and shearing occur between the premix particles. At the same time, the mechanical and chemical effects of the composite interface modifier and dispersant modify the fine powder during pulverization, thereby achieving continuous dispersion modification. The mixture is collected in a bag and connected to the finished product bin to obtain a modified filler for asphalt mixture with a D80 particle size of less than 10 μm.

[0031] Preferably, the microwave drying tunnel box in step (1) controls the free water content of the material to be less than 1% by adjusting the residence time of the material in the tunnel box; further preferably, the free water content of the material is controlled to be less than 0.5%; the microwave drying tunnel box is a non-stirring and non-contact drying method with a fast drying speed, and can effectively avoid the scattering of powder materials and prevent possible agglomeration, caking and adhesion, thereby ensuring the looseness and fluidity of the powder.

[0032] Preferably, the continuous airflow micronizer in step (2) is a gas vortex pulverizer or a SLG type continuous powder surface modifier.

[0033] The gas vortex pulverizer is mainly composed of a feed port, a pulverizing chamber, a grading wheel, a discharge port, and a drive system. When working, high-speed rotation generates high-speed airflow, forming a strong vortex in the pulverizing chamber. The material enters the pulverizing chamber quantitatively from the feed port. Under the action of the vortex, the material particles collide, rub and shear violently, thereby achieving refinement. At the same time, the mechanical and chemical effects during pulverization make the composite interface modifier and dispersant fully cover the filler, achieving continuous and efficient dispersion modification.

[0034] The SLG continuous powder surface modifier is mainly composed of a feed port, three continuous crushing chambers, a discharge port, a grading wheel, etc. The high-speed rotation of the rotor forces the powder material to be dispersed and refined, and continuously passes through three crushing chambers to form a secondary vortex, so that the composite interface modifier and dispersant act efficiently on the filler surface, and it has the functions of refinement, depolymerization and dispersion, and surface coating.

[0035] Further preferably, the classifying wheel speed of the continuous airflow micro-machine is controlled at 1500-2000rpm. The higher the classifying wheel speed, the smaller the modified filler particle size obtained at the terminal. By controlling the classifying wheel speed at 1500-2000rpm, the D80 particle size can be made less than 5μm, and the powder is discharged through the discharge port, while the larger particles continue to remain in the crushing chamber for cyclic crushing. When the micronized and dispersed modified filler is used to produce asphalt mixture, the surface area of ​​the modified filler is increased, the interface bonding ability of asphalt-aggregate is constructed, and it is easy to form asphalt cementing material with high bonding force.

[0036] The adhesion between asphalt and aggregate is mainly due to the polar molecules such as carboxylic acid contained in asphalt producing polar adsorption on the molecules on the surface of aggregate. Since water molecules have strong polarity and are more easily combined with acidic aggregates with negative surface charge potential, when asphalt is bonded to acidic aggregates, water molecules compete with asphalt for adsorbing aggregates, resulting in the peeling of asphalt film from the surface of acidic aggregates. In view of this, the modified filler of the present invention is mainly composed of limestone mineral powder, and is dispersed and modified by using composite interface modifiers and dispersants under the action of mechanical chemical effects by coordinating slaked lime, steel slag powder, phosphogypsum, and bauxite. The modified filler obtained has good compatibility with asphalt, greatly reduces the surface potential of aggregates, is easy to evenly adhere to aggregates, avoids the segregation of filler and aggregate, increases the wettability of asphalt to aggregates, can effectively coat the aggregate surface, enhance the adhesion between asphalt and aggregates, and resist water erosion.

[0037] According to a typical embodiment, the modified filler adhering to the aggregate is positive for eliminating the negative charge of the acidic aggregate, and thus the aggregate adhering to the modified filler has a stronger bond with the asphalt. This is mainly because the aggregate with the eliminated negative charge is easy to combine with the negative charge of the carboxylic acid in the asphalt, so that the asphalt is firmly bonded to the aggregate surface. As the negative charge potential of the aggregate decreases, the adsorption of water by the aggregate is greatly weakened, and it is difficult for water to penetrate the asphalt film barrier, thereby improving the asphalt's water damage resistance.

[0038] The modified filler of the present invention is added in proportion according to the type of asphalt mixture. The AC middle and lower pavement asphalt mixture is added in a metered amount of 2-4% of the total mass of the asphalt mixture. The SMA upper and surface asphalt mixture is added in a metered amount of 9-10% of the total mass of the asphalt mixture. Obviously, the amount of modified filler is small, and it can be packed in bags or cans for long-distance transportation, which is of great significance to promoting the use of local aggregates.

[0039] In summary, compared with the prior art, the present invention has the following advantages and beneficial effects:

[0040] (1) The modified filler of the present invention is prepared by mixing limestone powder, slaked lime, steel slag powder, phosphogypsum and bauxite. Compared with the use of limestone powder alone, the adhesion performance between aggregate and asphalt can be greatly improved, and the density, water stability, anti-stripping and high-temperature stability of asphalt mixture can be significantly improved.

[0041] (2) The present invention uniformly coats the filler with the composite interface modifier and dispersant under the action of the mechanochemical effect, thereby promoting good compatibility between the modified filler and asphalt, greatly reducing the surface potential of the aggregate, facilitating uniform adhesion of the aggregate, and avoiding segregation of the filler and the aggregate.

[0042] (3) The raw materials of the modified filler of the present invention are easily available and of low cost, and the modified production equipment is mature and easy to mass produce.

[0043] (4) The application of the modified filler of the present invention will make the range of aggregate selection for asphalt mixture wider, and local materials can be used, so that more types of aggregates can be used in asphalt mixture. DETAILED DESCRIPTION

[0044] In order to enable those skilled in the art to further understand the technical means, technical objectives and technical effects achieved by the present invention, the present invention is described in detail below in conjunction with the embodiments. However, the present invention is not limited in any form. It should be pointed out that for those skilled in the art, several adjustments and improvements can be made without departing from the concept of the present invention. These all belong to the protection scope of the present invention.

[0045] The technical parameters of the raw materials used are as follows (the raw materials without clear limiting parameters are all conventional raw materials understood in the art):

[0046] Limestone powder: D50 powder particle size <50μm.

[0047] Slaked lime: D50 particle size <50μm.

[0048] Phosphogypsum: D50 particle size <50μm.

[0049] Bauxite: D50 particle size <50μm.

[0050] Steel slag powder: D50 particle size <50μm, basicity 2.2; apparent density 2.63g / cm 3 ; The ingredients are shown in Table 1:

[0051] Table 1: Composition of steel slag powder:

[0052] Element CaO MgO <![CDATA[AL2O3]]> <![CDATA[SiO2]]> <![CDATA[Fe2O3]]> <![CDATA[P2O5]]> other Loss on ignition content(%) 37.65 9.22 4.62 15.28 19.96 2.8 9.78 0.69

[0053] Titanate coupling agent: JTW-101 monoalkoxy titanate coupling agent, provided by Nanjing Jingtianwei Chemical Co., Ltd.

[0054] Gas vortex mill: ACM-60 gas vortex mill, produced in Shengzhou, Zhejiang.

[0055] SLG continuous powder surface modification machine: provided by Jiangyin Qitai Non-metallic Engineering Co., Ltd.

[0056] Example 1

[0057] (1) After all raw materials are inspected and qualified, they are loaded in advance in each raw material warehouse according to the batch requirements; 35 parts of limestone powder, 30 parts of slaked lime, 18 parts of steel slag powder, 12 parts of phosphogypsum, and 8 parts of bauxite are automatically metered into a No. 1 high-speed mixer according to weight, mixed at a high speed of 700 rpm for 10 minutes, and transported to a microwave drying tunnel box through a fully enclosed pipeline system, the temperature is controlled at 120° C., and the materials are continuously dried until the free water content of the materials is less than 0.5%; to obtain a premix;

[0058] (2) The premix obtained in step (1), 0.8 parts of the composite interface modifier, and 0.3 parts of the dispersant sodium tripolyphosphate are added to the 2# high-speed mixer, and the mixture is dispersed at a high speed of 1000 rpm for 20 minutes, and then transported to the ACM-60 airflow vortex pulverizer through a fully enclosed pipeline system. The equipment has a single pulverizing chamber, and the continuous airflow fine machine classification speed is controlled to be 2000 rpm. The high-speed airflow is generated by high-speed rotation, and a vortex is formed in the pulverizing chamber. The premix enters the pulverizing chamber quantitatively from the feed port. Under the action of the vortex, the premix particles collide, rub and shear with each other, and at the same time as the pulverization, the mechanical and chemical effects cause the composite interface modifier and the dispersant to modify the fine powder, thereby realizing continuous dispersion modification; the mixture is connected to the finished product bin through a collecting bag to obtain a modified filler for asphalt mixture with a D80 particle size of less than 3 μm; wherein the composite interface modifier is a composite of aluminate coupling agent F-1 and sodium oleate in a mass ratio of 3:1.

[0059] Example 2

[0060] (1) After all raw materials are inspected and qualified, they are loaded in advance in each raw material warehouse according to the batch requirements; 40 parts of limestone powder, 25 parts of slaked lime, 19 parts of steel slag powder, 15 parts of phosphogypsum, and 8 parts of bauxite are automatically metered into a No. 1 high-speed mixer according to weight, mixed at a high speed of 700 rpm for 10 minutes, and transported to a microwave drying tunnel box through a fully enclosed pipeline system, the temperature is controlled at 120° C., and the materials are continuously dried until the free water content of the materials is less than 0.5%; to obtain a premix;

[0061] (2) The premix obtained in step (1), 0.6 parts of the composite interface modifier, and 0.5 parts of the dispersant sodium hexametaphosphate are added to the 2# high-speed mixer, and the mixture is dispersed at a high speed of 800 rpm for 20 minutes, and then transported to the ACM-60 airflow vortex pulverizer through a fully enclosed pipeline system. The equipment has a single pulverizing chamber, and the continuous airflow fine machine classification speed is controlled to be 1800 rpm. The high-speed airflow is generated by high-speed rotation, and a vortex is formed in the pulverizing chamber. The premix enters the pulverizing chamber quantitatively from the feed port. Under the action of the vortex, the premix particles collide, rub and shear with each other, and at the same time as the pulverization, the mechanical and chemical effects cause the composite interface modifier and the dispersant to modify the fine powder, thereby realizing continuous dispersion modification; the mixture is connected to the finished product bin through a collecting bag to obtain a modified filler for asphalt mixture with a D80 particle size of less than 4 μm; wherein the composite interface modifier is a composite of JTW-101 monoalkoxy titanate coupling agent and sodium oleate in a mass ratio of 2:1.

[0062] Example 3

[0063] (1) After all raw materials are inspected and qualified, they are loaded in advance in each raw material warehouse according to the batch requirements; 30 parts of limestone powder, 25 parts of slaked lime, 20 parts of steel slag powder, 15 parts of phosphogypsum, and 7 parts of bauxite are automatically metered into a No. 1 high-speed mixer according to weight, mixed at a high speed of 700 rpm for 10 minutes, and transported to a microwave drying tunnel box through a fully enclosed pipeline system, the temperature is controlled at 120° C., and the materials are continuously dried until the free water content of the materials is less than 0.5%; to obtain a premix;

[0064] (2) The premix obtained in step (1), 0.8 parts of the composite interface modifier, and 0.3 parts of the dispersant sodium hexametaphosphate are added to the 2# high-speed mixer, and the mixture is mixed and dispersed at a high speed of 800 rpm for 20 minutes, and then transported to the SLG type continuous powder surface modifier through a fully enclosed pipeline system. The equipment has three continuous crushing chambers, and the continuous airflow fine machine classification speed is controlled to be 1500 rpm. High-speed airflow is generated by high-speed rotation, and a vortex two-phase flow is formed. The composite interface modifier and dispersant are efficiently acted on the filler surface after passing through the three crushing chambers continuously, and the composite interface modifier and dispersant have the functions of refinement, depolymerization and dispersion, and surface coating. The mixed material is connected to the finished product bin through a collecting bag to obtain a modified filler for asphalt mixture with a D80 particle size of less than 4 μm. The composite interface modifier is a composite of JTW-101 type monoalkoxy titanate coupling agent, aluminate coupling agent F-3, and sodium oleate in a mass ratio of 2:1:1.

[0065] Example 4

[0066] (1) After all raw materials are inspected and qualified, they are loaded in advance in each raw material warehouse according to the batch requirements; 40 parts of limestone powder, 30 parts of slaked lime, 20 parts of steel slag powder, 10 parts of phosphogypsum, and 5 parts of bauxite are automatically metered into a No. 1 high-speed mixer according to weight, mixed at a high speed of 700 rpm for 10 minutes, and transported to a microwave drying tunnel box through a fully enclosed pipeline system, the temperature is controlled at 120° C., and the materials are continuously dried until the free water content of the materials is less than 0.5%; to obtain a premix;

[0067] (2) The premix obtained in step (1), 0.5 parts of the composite interface modifier, and 0.4 parts of the dispersant sodium tripolyphosphate are added to the 2# high-speed mixer, and the mixture is mixed and dispersed at a high speed of 800 rpm for 20 minutes, and then transported to the SLG type continuous powder surface modifier through a fully enclosed pipeline system. The equipment has three continuous crushing chambers, and the continuous airflow fine machine classification speed is controlled to be 1800 rpm. High-speed airflow is generated by high-speed rotation, and a vortex two-phase flow is formed. The composite interface modifier and dispersant are efficiently acted on the filler surface after passing through the three crushing chambers continuously, and the composite interface modifier and dispersant have the functions of refinement, depolymerization and dispersion, and surface coating. The mixed material is connected to the finished product bin through a collecting bag to obtain a modified filler for asphalt mixture with a D80 particle size of less than 3 μm. The composite interface modifier is a composite of JTW-101 type monoalkoxy titanate coupling agent and sodium oleate in a mass ratio of 2:1.

[0068] Comparative Example 1

[0069] The modification was carried out with reference to the raw material ratio and method of Example 1, except that the use of steel slag powder was eliminated and replaced with limestone ore powder.

[0070] Comparative Example 2

[0071] The raw material ratio and method of Example 1 were modified, except that the use of the dispersant was eliminated.

[0072] Comparative Example 3

[0073] The modification was carried out with reference to the raw material ratio and method of Example 1, except that the use of bauxite was eliminated and replaced with limestone powder.

[0074] Comparative Example 4

[0075] The modification was carried out with reference to the raw material ratio and method of Example 1, except that the use of slaked lime was eliminated and replaced with limestone powder.

[0076] Comparative Example 5

[0077] The modification was carried out with reference to the raw material ratio and method of Example 1, except that the use of phosphogypsum was eliminated and replaced with limestone powder.

[0078] Comparative Example 6

[0079] (1) After all raw materials are inspected and qualified, they are loaded in advance in each raw material warehouse according to the batch requirements; 35 parts of limestone powder, 30 parts of slaked lime, 18 parts of steel slag powder, 12 parts of phosphogypsum, and 8 parts of bauxite are automatically metered into a No. 1 high-speed mixer according to weight, mixed at a high speed of 700 rpm for 10 minutes, and transported to a microwave drying tunnel box through a fully enclosed pipeline system, the temperature is controlled at 120° C., and the materials are continuously dried until the free water content of the materials is less than 0.5%; to obtain a premix;

[0080] (2) Add the premix obtained in step (1), 0.8 parts of the composite interface modifier, and 0.3 parts of the dispersant sodium tripolyphosphate into a 2# high-speed mixer, and mix and disperse at a high speed of 1000 rpm for 20 minutes to obtain a modified filler for asphalt mixture; wherein the composite interface modifier is a composite of aluminate coupling agent F-1 and sodium oleate in a mass ratio of 3:1.

[0081] In Comparative Example 6, no air flow mill was used to mechanically and chemically treat the filler. The filler particle size was coarse and the dispersibility was poor. The interface effect between the filler and asphalt and aggregate was affected, which was manifested in the reduced adhesion of the modified filler when used in asphalt mixture.

[0082] Comparative Example 7

[0083] The modification was carried out according to the raw material ratio and method of Example 1, except that no composite interface modifier was added.

[0084] Comparative Example 8

[0085] The modification was carried out according to the raw material ratio and method of Example 1, except that sodium oleate was not used in the composite interface modifier.

[0086] Comparative verification of the effect of modified fillers on improving the performance of asphalt mixtures: The modified fillers of Examples 1-4 and Comparative Examples 1-8 are used in asphalt mixtures to improve the bonding ability of asphalt and granite aggregates. 13# is an asphalt mixture without any mineral powder or filler; 14# is an asphalt mixture with only limestone mineral powder. Marshall test specimens are made to conduct comprehensive tests such as water immersion residual stability, freeze-thaw splitting strength ratio, Kentburgh water immersion and dispersion loss rate, and rutting dynamic stability to measure the bonding performance and water stability of asphalt and aggregates. Specific sample preparation and testing are as follows:

[0087] (I) Basic asphalt raw material: 70#A grade asphalt, performance parameters are shown in Table 2.

[0088] Table 2 Performance parameters of 70#A grade asphalt

[0089] Test items Test Data Test methods Needle penetration (25℃) / 0.1mm 74 T0604 "Asphalt Penetration Test" Softening point / ℃ 47 T0606 "Asphalt softening point test (ring and ball method)" Elongation (10℃) / cm 40 T0605 "Asphalt ductility test" Elongation (15℃) / cm 132 T0605 "Asphalt ductility test"

[0090] (ii) Coarse aggregate: Select granite acidic coarse aggregate, and the aggregate gradation ratio shall refer to the AC-20 target mix design, as shown in Table 3.

[0091] Table 3 Coarse aggregate gradation ratio

[0092] Granite acidic coarse aggregate particle size range Grading ratio 16-19mm 14.3% 13.2-16mm 21.6% 9.5-13.2mm 14.1% 4.75-9.5mm 27.7% 2.36-4.75mm 22.3%

[0093] (III) Fine aggregate: Select granite acid fine aggregate, and the aggregate gradation ratio shall refer to the AC-20 target mix design, as shown in Table 4.

[0094] Table 4 Fine aggregate gradation ratio

[0095]

[0096]

[0097] (IV) Asphalt mixture formula, as shown in Table 5.

[0098] Table 5 Asphalt mixture formula

[0099]

[0100]

[0101] (V) Preparation of Marshall samples: Mix the modified filler or limestone powder with the granite acid coarse aggregate and fine aggregate evenly, preheat the aggregate to 180°C and the asphalt to 158°C, then mix evenly at 160°C, then put the mixture into the Marshall test mold, and compact it 50 times on both sides at 145°C according to the Marshall compaction molding method to form a standard size test piece.

[0102] (VI) Water immersion Marshall stability test:

[0103] In the test, the residual stability of each group of test water immersion Marshall was tested according to the provisions of the Technical Specifications for Highway Asphalt Pavement Construction (JTG F40-2023). The specimen was kept in a 60℃ water tank for 30 minutes, and the tested Marshall stability was used as the standard Marshall stability MS0; the specimen was kept in a 60℃ water tank for 48 hours, and the tested stability was the water immersion Marshall stability MS1. The ratio of the water immersion Marshall stability to the standard Marshall stability (MS1 / MS0) × 100% was the residual stability. If the residual stability was greater than 80%, it could be judged to have good water stability. The test results are shown in Table 6.

[0104] (VII) Freeze-thaw splitting strength ratio test:

[0105] One group of specimens was immersed in a constant temperature water bath at 25℃ for 2 hours, and its basic splitting strength was tested and recorded as R0; another group of specimens was immersed in a constant temperature water bath at 25℃ for 2 hours, and then immersed in water and vacuumed for 15 minutes to fully saturate and absorb water, and then the specimens were placed in a -18℃ refrigerator for 16 hours, and immediately placed in a 60℃ constant temperature water tank for 24 hours after freezing, and then immersed in 20℃ water for 0.5 hours to test its splitting strength, recorded as R1; the water stability of asphalt mixture in harsh high and low temperature environments was evaluated by the splitting strength ratio before and after the freeze-thaw splitting test (R1 / R0)×100%. If the freeze-thaw splitting strength ratio is greater than 75%, it can be judged to have good water stability. The test results are shown in Table 6.

[0106] Table 6 Test results of residual stability and freeze-thaw splitting strength ratio of Marshall specimens of asphalt mixture after immersion in water

[0107]

[0108]

[0109] (VIII) Kentburgh immersion and dispersion test:

[0110] The test was conducted in accordance with T0733-2011 of JTG E20-2011 "Testing Procedures for Asphalt and Asphalt Mixtures in Highway Engineering". The specimen was immersed in a water tank at 60℃ for 48h, then placed at room temperature for 24h, and the mass was weighed and recorded as m0; then, the specimen was placed in a Los Angeles test machine and rotated and hit the number of times specified, and the remaining mass of the specimen after the test was weighed m1, and the percentage of the mass of the asphalt mixture specimen scattered was used to represent the scattering loss. It better simulated the degree of separation and loss of asphalt mixture from aggregates under the erosion of water. The test results are shown in Table 7.

[0111] (IX) Anti-rutting test:

[0112] Under high temperature conditions, the specimen deforms when subjected to standard load axle load. The number of times the standard axle load rolls for each 1mm deformation is taken as the dynamic stability. This is used to evaluate the anti-rutting ability of asphalt mixture. The rutting test specimen is 300mmx300mmx50mm. During the experiment, a wheel load of 0.7MPa is applied at 60℃ for 1h. The test results are shown in Table 7.

[0113] Table 7 Test results of Kentburgh water immersion dispersion rate and anti-rutting dynamic stability of asphalt mixture

[0114]

[0115]

[0116] The above Marshall test comprehensively evaluates the high temperature stability, water stability and anti-rutting performance of the asphalt mixture through the residual stability of the specimen after immersion, the freeze-thaw splitting strength ratio, and the Kentburgh immersion and dispersion test. The modified filler of the present invention is obviously excellent in improving the bonding between granite aggregate and asphalt. The residual stability after immersion is maintained at more than 94%, and the freeze-thaw splitting strength ratio is maintained at more than 92%, which fully meets the technical requirements of road asphalt mixture. In particular, the Kentburgh immersion and dispersion test can better reflect the bonding strength and resistance to water damage of the asphalt mixture by simulating the degree of peeling and dispersion of asphalt from aggregates under the erosion of water.

[0117] By comparing the modified fillers (1#-4#) of the present invention with the control group (6#-14#), the synergistic assistance of each raw material and the mechanical chemical modification have a significant effect on improving the water stability of the modified filler used for aggregates. This is because the modified fillers are evenly dispersed, have improved compatibility, and evenly adhere to the aggregate surface to reduce the surface potential of the negatively charged aggregate, thereby constructing good interface properties, thereby improving the bonding force between the aggregate and asphalt, which is obvious in promoting the high temperature stability, water stability, and rutting resistance of the asphalt mixture.

[0118] It should be understood that any technical solution that can be obtained by technicians in this technical field through logical analysis, reasoning or limited experiments based on the concept of the present invention on the basis of the existing technology should be within the protection scope determined by the claims.

Claims

1. A modified filler for asphalt mixture, characterized in that: The modified filler is composed of the following raw materials in parts by weight: 30-40 parts of limestone powder, 25-35 parts of slaked lime, 15-20 parts of steel slag powder, 10-15 parts of phosphogypsum, 5-8 parts of bauxite, 0.5-0.8 parts of composite interface modifier, and 0.3-0.5 parts of dispersant; wherein: The composite interface modifier is a composite of a titanate coupling agent and / or an aluminate coupling agent and sodium oleate in a mass ratio of 1-3:1; The dispersant is at least one of sodium tripolyphosphate and sodium hexametaphosphate; The modified filler for asphalt mixture is prepared by the following method: (1) adding limestone powder, slaked lime, steel slag powder, phosphogypsum and bauxite into a 1# high-speed mixer and mixing them uniformly; conveying them to a microwave drying tunnel box through a fully enclosed pipeline system, and drying them at a controlled temperature of 120-130° C. to obtain a premix; (2) The premix, composite interface modifier and dispersant are added to the No. 2 high-speed mixer and mixed evenly. The mixture is then transported to the continuous airflow fine machine through a fully enclosed pipeline system. The classification speed of the continuous airflow fine machine is controlled to generate a high-speed airflow through high-speed rotation, forming a vortex in the pulverizing chamber. The premix enters the pulverizing chamber quantitatively from the feed port. Under the action of the vortex, the composite interface modifier and dispersant are modified into fine powders by mechanical and chemical effects, thereby achieving continuous dispersion modification. The mixture is collected in a bag and connected to a finished product bin to obtain a modified filler for asphalt mixture with a D80 particle size of less than 10 μm.

2. The modified filler for asphalt mixture according to claim 1, characterized in that: The D50 particle size of the limestone powder is less than 50 μm; the D50 particle size of the slaked lime is less than 50 μm; the D50 particle size of the steel slag powder is less than 50 μm; the D50 particle size of the phosphogypsum is less than 50 μm; and the D50 particle size of the bauxite is less than 50 μm.

3. The modified filler for asphalt mixture according to claim 1, characterized in that: The composite interface modifier is a composite of a titanate coupling agent and sodium oleate in a mass ratio of 2:

1.

4. The modified filler for asphalt mixture according to claim 1, characterized in that: The composite interface modifier is a composite of an aluminate coupling agent and sodium oleate in a mass ratio of 3:

1.

5. The modified filler for asphalt mixture according to claim 1, characterized in that: The composite interface modifier is a composite of a titanate coupling agent, an aluminate coupling agent and sodium oleate in a mass ratio of 2:1:

1.

6. The modified filler for asphalt mixture according to claim 1, characterized in that: The titanate coupling agent is a chelate titanate coupling agent.

7. The modified filler for asphalt mixture according to claim 1, characterized in that: The titanate coupling agent is a monooxyalkyl titanate coupling agent.

8. A method for preparing the modified filler for asphalt mixture according to any one of claims 1 to 7, characterized in that: The specific preparation method is as follows: (1) adding limestone powder, slaked lime, steel slag powder, phosphogypsum and bauxite into a 1# high-speed mixer and mixing them uniformly; conveying them to a microwave drying tunnel box through a fully enclosed pipeline system, and drying them at a controlled temperature of 120-130° C. to obtain a premix; (2) The premix, composite interface modifier and dispersant are added to the No. 2 high-speed mixer and mixed evenly. The mixture is then transported to the continuous airflow fine machine through a fully enclosed pipeline system. The classification speed of the continuous airflow fine machine is controlled to generate a high-speed airflow through high-speed rotation, forming a vortex in the pulverizing chamber. The premix enters the pulverizing chamber quantitatively from the feed port. Under the action of the vortex, the composite interface modifier and dispersant are modified into fine powders by mechanical and chemical effects, thereby achieving continuous dispersion modification. The mixture is collected in a bag and connected to a finished product bin to obtain a modified filler for asphalt mixture with a D80 particle size of less than 10 μm.

9. The method for preparing a modified filler for asphalt mixture according to claim 8, characterized in that: In the microwave drying tunnel box in step (1), the free water content of the material is controlled to be less than 1%.

10. The method for preparing a modified filler for asphalt mixture according to claim 8, characterized in that: The rotating speed of the classifying wheel of the continuous airflow micro-machine in step (2) is controlled at 1500-2000 rpm.

Citation Information

Patent Citations

  • Asphalt concrete filler, and asphalt concrete and preparation method thereof

    CN114014570A

  • Micron-sized anti-stripping agent for acidic aggregate asphalt mixture and use method of micron-sized anti-stripping agent

    CN114133154A

  • Steel slag powder modified ardealite-based filler, preparation method thereof, asphalt mixture and preparation method thereof

    CN116253530A

  • Modified mineral aggregate for bituminous pavement and method for producing same

    CN1837130A

  • Asphalt-coated filler and its production

    JP1996059318A

Cited By

  • Asphalt concrete filler, asphalt concrete and preparation method of asphalt concrete filler

    CN120736821A